GENETIC ASPECTS OF ADULT OBESITY FORMATION - Варвара Ивановна Минина; Анастасия Александровна Яковлева; Анастасия Валерьевна Понасенко; Ольга Александровна Соболева; Анастасия Владимировна Торгунакова; Елена Александровна Киселева; Лидия Александровна Варич; Татьяна Андреевна Толочко; Анна Дмитриевна Веснина; Игорь Анатольевич Те; Яна Александровна Захарова (Medicina v Kuzbasse, 2023)
Obesity is a multifactorial disease, and the genetic component occupies an important place in its pathogenesis. One of the most studied and closely associated with monogenic obesity is the FTO (fat mass and obesity associated) gene. At the same time, inherited variants of genes related to the control of lipid metabolism (ADRB2, ADRB3), fatty acid oxidation (PPARG) and its transfer across cell membranes into intestinal cells (FABP2), inflammatory processes (IL6, IL8, TNF, CRP, TLR2), as well as variants of lipoprotein (LPA) and leptin (LEPR) genes may be of great importance in the formation of obesity in adults. Purpose – to study the contribution of polymorphisms of FTO, ADRB2, ADRB3, FABP2, PPARG, IL6, IL8, TNF, CRP, TLR2, LPA and LEPR genes to the risk of obesity development in Kuzbass residents. Materials and methods. 256 middle-aged and elderly people living in Kuzbass, an industrial region of Siberia, were examined. 14 variants in 13 genes were selected for genotyping: FTO rs9939609, ADRB2 rs1042713, ADRB3 rs4994, FABP2 rs1799883, PPARG rs1801282, IL6 rs2229238, IL18 rs1946518, CXCL8 rs4073 and rs2227306, TNF rs1800629, CRP rs1130864, TLR2 rs3804099, LPA rs10455872 and LEPR rs1137100. Results. Genes whose variants were statistically significantly associated with the risk of developing obesity were identified (recessive inheritance model: FTO rs9939609 (OR 1. 88 95% CI (1.03-3.42) p = 0.039) and IL18 rs1946518 (OR 0.44 95% CI (0.23-0.88) p = 0.015); dominant inheritance model: IL6R rs2229238, OR 1.81 95% CI (1.10-3.00) p = 0.02). Conclusion. This study found associations between inherited variants of FTO, IL18, IL6R genes and risk of obesity in adults.